Analisis Faktor-faktor yang Mempengaruhi Kinerja Reksadana Pendapatan Tetap Syariah di Indonesia Periode 2019-2023 - Fredean Fahenzi Kholid; Elyanti Rosmanidar; Eja Armaz Hardi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In this research. conducted a study Analysis of Factors Affecting the Performance of Fixed Income Mutual Funds Sharia in Indonesia for the 2019-2023 Period. In this study using Quantitative methods and the data analysis method used is Multiple Linear Regression. Research results The results showed that inflation, exchange rates, and interest rates gave a negative significant value, so it does not contribute well to sharia fixed income mutual funds, while the money supply has a positive effect. while the amount of money in circulation has a positive effect on sharia fixed income mutual funds. The results of the calculation of the coefficient of determination shows that 43.1% of the value of Islamic fixed income mutual funds is influenced by inflation, exchange rates, money supply and interest rates.